Acetone erosion and its effect mechanism on pores and fractures in coal. (1st October 2019) - Wang, Zheng; Lin, Baiquan; Li, He; Hong, Yidu; Yang, Wei; Zhu, Xiangnan; Liu, Yanchi
Abstract: Nowadays, coalbed methane recovery faces challenges such as high gas content, micro-porosity and low permeability. An exploratory study on improving coal porosity by acetone treatment was carried out. Pore size distribution and fracture development before and after acetone treatment were evaluated using a suite of integrated diagnostic techniques including rock acoustical test, weight analysis, Scanning Electron Microscope (SEM), Nuclear Magnetic Resonance (NMR), Fourier Transform Infrared Spectroscopy (FT-IR) and mercury intrusion porosimetry (MIP). After acetone treatment, micropores are partially converted into mesopores and macropores. The porosity of coal increases by 2.66% after acetone treatment. Functional groups including hydroxy, methylene, oxygen functional groups and aromatic hydrocarbons reduce significantly and the removal of these hydrophilic groups significantly weakens the hydrophilicity of coal. New fractures appeared within 32.89% of the eroded zone, even large through-going fractures may appear after acetone treatment. The results indicate that acetone treatment is effective in improving gas productivity thus has the potential to become a new coalbed methane reservoir stimulation technology.